Oxidation of Hass Avocado Seed Starch for the Development of Films with Microcrystalline Cellulose - Yánez-Romero, Maria Elena; Cedeño-Sares, Luis Alberto; Macas-Jiménez, Dayana; Vidal-Zapata, Melissa; Brito-Moína, Hanníbal Lorenzo; Lapo-Calderón, Byron; Beltrán-Balarezo, Carolina (Revista de Ciências Agroveterinárias, 2025)
This study focused on the development of films based on oxidized starch extracted from Hass avocado seeds with microcrystalline cellulose, as an alternative to conventional plastics to reduce environmental impact. The neat starch was extracted and then subjected to an oxidation process with sodium hypochlorite at different reaction times to improve the physical and functional properties of the films. The reaction time significantly influenced the chemical composition and functional properties of the starch. Starch with a high degree of oxidation (with carbonyl group of 0,029% ± 0,002 and carboxyl group of 0,078% ± 0,003) was selected for film formulation, and an experimental factorial design was conducted to determine the most suitable percentages of D-sorbitol and microcrystalline cellulose to minimize film moisture and solubility and improve water vapor permeability (WVP). It was found that the most suitable percentages of D-sorbitol and microcrystalline cellulose were 1,5% and 0,2% w/v, respectively, to minimize film moisture and solubility; whereas, for WVP they were 1,5% and 0,1% w/v, respectively. However, the results obtained in minimizing film moisture and solubility were very close to those yielded by the percentages 1,5% and 0,2% w/v. In conclusion, this study demonstrated the possibility of using oxidized starch from Hass avocado seeds for film production, with D-sorbitol and microcrystalline cellulose at 1,5% and 0,1% w/v, respectively.